SISTEM AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS GUNA MENDUKUNG PENGENDALIAN INTERN PADA KANTOR KECAMATAN SUNGAI PINYUH - Amelia Amelia (Jurnal Ekonomi Integra, 2020)
This study conducted to determine The Accounting Systems Cash Revenues and Expenses applied to Sungai Pinyuh District Office to improve the office internal control in order to achive office’s goal. Cash revenues and cash expenses are two conditions that affect operatinal activities of the office. Method used in this research is descriptive research. Focus of this research is accounting system of cash revenues and expenses in Sungai Pinyuh District Office especially related functions, forms that is used, flowchart procedures, and internal controls of the company. Based on the results of data analysis, it was found that the recording system has fulfilled the provision that applied, all cash revenues and expenses at the Sungai Pinyuh District Office are directly linked and examined by the relevant regional agencies so that there is very little risk of leakage of funds or funds that are not desired by the government.